Prognostic factors for long‐term survival following complete resection by lobectomy in stage I non‐small cell lung cancer. Issue 20 (30th August 2022) - Galata, Christian; Messerschmidt, Antje; Kostic, Marko; Karampinis, Ioannis; Roessner, Eric; El Beyrouti, Hazem; Schneider, Thomas; Stamenovic, Davor
Abstract: Background: The aim of this study was to evaluate predictors for long‐term overall survival (OS) in patients with stage I non‐small cell lung cancer (NSCLC). Methods: All patients undergoing complete resection by lobectomy for stage I NSCLC between October 2012 and December 2015 at a single center were included. Univariable and multivariable Cox regression analyses were performed to identify prognostic factors. Results: A total of 92 patients were included. Univariable and multivariable Cox regression analyses revealed preoperative neutrophil to lymphocyte ratio (NLR, p = 0.005), preoperative diffusion capacity of the lungs for carbon monoxide (DLCO, p = 0.010) and forced expiratory volume in 1 second (FEV1, p = 0.041) as well as male gender ( p = 0.026) as independent prognostic factors for OS. Combining the calculated cutoff values for FEV1 (<73.0%) and NLR (>3.49) into one parameter resulted in a highly significant difference in survival times when stratified by this variable. Conclusions: Recently, much emphasis has been put on the prognostic importance of blood biomarkers in NSCLC. In our study, NLR was an independent factor for OS, as were baseline characteristics such as DLCO, FEV1, and gender. Further studies on the association of biomarkers for systemic inflammation and lung function parameters with respect to patient survival are warranted. Abstract : A key issue in the analysis of survival data of patients with lung cancer is the identification of risk factors for a poor outcome as defined as death due to the disease. This retrospective study aimed to investigate the significance of both known prognostic factors such as lung function parameters and newer predictors of survival such as the neutrophil to lymphocyte ratio in a cohort of stage I lung cancer patients who underwent complete resection by lobectomy followed by radical lymphadenectomy. In this study, both lung function parameters and neutrophil to lymphocyte ratio were independent predictors of patient survival. However, none of these factors was shown to be superior in predicting a fatal outcome.